Predictive factors of lethality and complications of deep fascial space infections of the neck - SUEHARA,ALEXANDRE BABÁ (2020)
ABSTRACT Objective: to identify predictive factors for lethality and complications of deep fascial space infections of the neck (DFSIN), establishing an early and aggressive treatment in the neck before the progression to descending mediastinitis. Methods: we retrospectively analyzed 133 cases of DFSIN treated at Discipline of Head and Neck Surgery of the Medicine School of Santa Casa de Misericórdia de São Paulo. We accessed demographic characteristics, associated diseases, clinical presentation, laboratorial tests, length of hospital stay, number of involved anatomic neck spaces, intra-operative and microbiology findings. We analyzed these data using logistic regression to predict DFSIN lethality and life threatening complications (mediastinitis, septic shock, pneumonia, pleural empyema, skin necrosis). Results: lethality and complication ratios were 9% and 50.3%, respectively. The logistic regression model showed that patients with septic shock were more likely to have progression to death (p < 0.001) and, the presence of more than two involved neck spaces (p < 0.001) and older individuals (p = 0.017) were more likely to have complicated deep neck infections. Descending necrotizing mediatinitis increased the lethality ratio by 50%, and was associated to necrotizing fasciitis (p=0.012) and pleural empyema (p<0.001). Conclusion: septic shock is a lethal predictive factor and age as well as more than two involved neck spaces are the predictive factors for complications. Necrotizing fasciitis is an important factor for complications and death. Therefore, its surgical treatment must be more aggressive. Descending mediastinitis has a high lethal rate and the successful treatment is based on early diagnosis and aggressive surgical approach.